Valuing start-ups – selected approaches and their modification based on external factors - Dusatkova, Martina Skalicka; Zinecker, Marek (Business: Theory and Practice, 2016)
The recent methods of start-up valuation seek to compensate for the lack of data necessary for a standard company valuation with additional information on the person of the entrepreneur and business project. None of the existing approaches, however, takes into consideration information about the environment in which the venture capitalists conduct their investments. Therefore, the aim of this paper is to develop an approach considering factors of the investee companies’ environment. Such a modification will allow a more accurate estimate of the value of the projects investigated. The nature of this study is explorative. It relies on secondary data that was collected using interviews and semi-structured questionnaires in previous empirical studies. During the course of the modelling process, information on the quality of the investee companies’ environment expressed is incorporated into the established start-up project valuations. Our original proposal consists of the modification of the β coefficient calculation for a given type of projects. An essential part of this modification is also a proposal for the extension of the project scoring characteristics to include expert estimates and, in the case of regression analysis, the inclusion of explanatory variables expressing the suitability of the environment for venture capital investments.